Life attributes of Zygogramma bicolorata Pallister (Coleoptera: Chrysomelidae): challenges and future directions. Issue 2 (1st February 2020) - Patel, Priya; Bhusal, Daya Ram; Kumar, Bhupendra; Kumar, Dinesh
ABSTRACT: Parthenium hysterophorus L. (Asteraceae) is an alien herbaceous weed with a pantropical distribution. The weed adversely affects grazing land productivity, native biodiversity and causes respiratory and dermal allergies in humans. The weed continues to invade new countries, with increases in CO2 set to further enhance this spread. Biological control is among the most cost-effective management strategy for P. hysterophorus, with the leaf-feeding beetle Zygogramma bicolorata Pallister (Coleoptera: Chrysomelidae) among the most promising candidates. Our review discusses the life cycle and feeding and reproductive behaviours of Z. bicolorata . We emphasise how abiotic factors and biological processes, viz. ageing, rhythmicity, multiple matings and interactions amongst species, influence the fertility and mortality parameters of the beetle. We anticipate that this review will assist in improving the strategies for rapid mass-multiplication of Z. bicolorata in laboratories. In addition, the review will support efforts to develop classical biological control approaches in regions where Parthenium is invasive.